NO TIME LIKE THE PRESENT - Esch, Deborah (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1993)
This essay approaches the question of the critical analysis of TV on the basisof the temporality of the televisual medium. Discussion of Cavell, de Manand Kernan on massmedia.